A METHODOLOGY FOR DEVELOPMENT SYSTEM OPTIMIZATION OF A HYDROCARBON ASSET BASED ON AN INTEGRATED ADAPTIVE GEOLOGICAL MODEL - Murodov Sadriddin Nizomiddinovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This paper proposes a comprehensive methodology for optimizing the development system of mature fields with high reservoir heterogeneity. The methodology is based on the sequential integration of new geological and technological data and hydrodynamic simulation results into an updated three-dimensional static model. An algorithm for model adaptation to dynamic data is considered, allowing for a reduction in uncertainty in the prediction of filtration-capacity properties. The implementation of the methodology enables a quantitative assessment of the efficiency of various development scenarios, including changes to the well pattern and operating modes. The result is a justified plan of measures aimed at increasing the oil recovery factor (ORF) and the economic efficiency of the project.